Depiction of Chamunda on the exterior wall of the Shiva Temple - Temples of India Project Team (Jio Institute, 2024)
Seen here is the east-facing exterior wall of the Shiva Temple. All the wall projections are adorned with sculptures. The bhadra (central projection) has a sculpture of Chamunda, the intermediate projections have surasundaris (celestial damsels), and the corner projections have dikpalas (deities for cardinal directions). Chamunda is shown in skeletal form. There is a recess separating the main shrine wall and the mandapa (pillared hall), which has a kutastambha motif (a pilaster with miniature shikhara or superstructure).